SOCIO-PSYCHOLOGICAL MECHANISMS OF THE INCLUSIVE EDUCATION PROCESS IN GENERAL EDUCATION SCHOOLS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
The paper examines the socio-psychological mechanisms involved in implementing inclusive education within general education schools. Inclusive education refers to integrating students with disabilities or special needs into mainstream schools, allowing for equal learning opportunities for all students. The study explores various psychological and social factors that affect this process, such as attitudes of teachers, students, and parents, and the role of school culture in facilitating or hindering inclusion. The article also discusses challenges and offers recommendations for creating an effective and supportive learning environment for all students, regardless of their abilities.